Prevention study on defective solid expandable tubular fracture. (March 2021) - Shi, Changshuai; Chen, Kailin; Zhu, Xiaohua; Fu, Daqi; Qi, Yuekui; Li, Jianan; Cheng, Feilong
Highlights: Carrying out the scanning electron microscope (SEM) test of the fracture section. Reveal the fracture failure mechanism of solid expandable tubular (SET). The finite element model of the defective expandable tubular is established. The results provide a theoretical basis for preventing the fracture of SET. Abstract: This study aims to reveal the failure mechanism of solid expandable tubular (SET) in a laboratory experiment and avoid downhole application failure. The scanning electron microscope (SEM) test of the section is carried out, and the finite element model of the defective expandable tubular is established. It was found that the tube defect causes the rupture failure of the expansion tube in the laboratory experiment, and the failure with defects in the inner wall occurs mostly. The safety and reliability of metal materials 316L and 304 are better than 20G and SA106b. Flaw detection shall ensure that the tube wall thickness is larger than 3.6 mm at any position. Moreover, rubber rings number and defect length have little effect on the bulging performance. The results provide a theoretical basis for preventing the fracture of SET.